FREQUENCY AND THE RELATED SOCIO-DEMOGRAPHIC AND CLINICAL FACTORS OF PHANTOM LIMB PAIN IN TRAUMATIC AMPUTEES PRESENTING AT A TERTIARY CARE REHABILITATION SETUP: Phantom Limb Pain in Traumatic Amputees - Ayaz, Saeed Bin; Ikram, Muhammad; Matee, Sumeera; Fahim, Muhammad; Khan, Atif Ahmed; Ahmad, Mahmood (Pakistan Armed Forces Medical Journal, 2015)
Objective: To find out the frequency of phantom limb pain (PLP) in a sample of Pakistani amputee population presenting with amputation due to trauma and to investigate its relationship with different socio-demographic  and clinical factors.Study Design: A cross-sectional descriptive study.Place and Duration of Study: Armed Forces Institute of Rehabilitation Medicine, Rawalpindi from August 2010 to October 2013.Material and Methods: Through non-probability purposive sampling, patients of both genders and all ages having a traumatic etiology of amputation were sampled from the outdoor amputee clinic and the indoor amputee ward. Patients having diabetes mellitus, polyneuropathy, memory loss, cognitive deficits and established history of psychiatric disorders were excluded. Through face to face semi structured interviews, information was obtained about presence of PLP, gender, location (urban or rural), ethnicity based on Pakistani provinces (Punjab, Sindh, Khyber Pakhtunkhwa, Balochistan, Azad Jammu and Kashmir), monthly income in Pakistani Rupees (PKR) (